OPERASI PLASTIK DALAM AL-QUR'AN: INTERPRETASI MA'NA-CUM-MAGHZA Q.S. AN-NISA: 119 - Tesa Maulana; Aji Mustofa; Munawir (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This study aims to reconstruct the interpretation of Surah An-Nisa: 119 and reveal the verse significance to the legal relevance of plastic surgery. This study uses a qualitative method with a ma’na-cum-maghza hermeneutic approach to seek the meaning and significance of verse in the modern era. The result of this study stated that Surah An-Nisa: 119, it is not right to legalize the prohibition of plastic surgery. Based on ma’na and maghza, Surah An-Nisa: 119 is changing the religious law system, and the physical form of humans or animals is legal as long as it is within the maqashid Syariah corridor. Based on its purpose, the law on plastic surgery is divided into halal or permissible if it is done to treat and beautify oneself without damaging and eliminating organ function and haram or prohibited if it is done to change human nature, such as castration or changing genitals